Games as an Intervention for Adolescent Mental Health: A systematic literature review using PRISMA - Hariyadi, Sigit; Mulawarman, Mulawarman; Mulyani, Petra Kristi; Awalya, Awalya (Universitas Nahdlatul Ulama Blitar, 2025)
The phenomenon of adolescent mental health is increasingly becoming a public concern, especially with the increasing cases of depression and suicide in various regions. This study aims to explore the use of video games as an intervention to support adolescent mental health. The method used was a systematic literature review (SLR) with the PRISMA approach, which involved identifying, screening, and evaluating related articles from databases such as Scopus, Taylor & Francis, and ScienceDirect. A total of 12 articles were selected that met the inclusion and exclusion criteria. The results showed various game variants that can be used as mental health interventions, including smartphone-based games, virtual reality (VR), board games, and role-playing games. The impact of game use included reduced depression and anxiety symptoms, improved social-emotional skills, and improved adolescent cognitive functioning. The study emphasizes the crucial role of collaboration between schools, families, and communities to develop gaming programs for students at risk of mental health problems, making the audience feel the importance of their collective efforts in addressing this issue.